Maternal periodontal disease in rats decreases insulin sensitivity and insulin signaling in adult offspring - Shirakashi, Daisy J. [UNESP]; Leal, Rosana P. [UNESP]; Colombo, Natalia H. [UNESP]; Chiba, Fernando Y. [UNESP]; Garbin, Cléa A.S. [UNESP]; Jardim Jr., Elerson G. [UNESP]; Silva, Cristina Antoniali [UNESP]; Sumida, Doris Hissako [UNESP] (Wiley, 2013)
Background: Periodontal disease during pregnancy has been recognized as one of the causes of preterm and lowbirth- weight (PLBW) babies. Several studies have demonstrated that PLBW babies are prone to developing insulin resistance as adults. Although there is controversy over the association between periodontal disease and PLBW, the phenomenon known as programming can translate any stimulus or aggression experienced during intrauterine growth into physiologic and metabolic alterations in adulthood. The purpose of the present study is to investigate whether the offspring of rats with periodontal disease develop insulin resistance in adulthood. Methods: Ten female Wistar rats were divided into periodontal disease (PED) and control (CN) groups. All rats were mated at 7 days after induction of periodontal disease. Male offspring were divided into two groups: 1) periodontal disease offspring (PEDO; n = 24); and 2) control offspring (CNO; n = 24). Offspring body weight was measured from birth until 75 days. When the offspring reached 75 days old, the following parameters were measured: 1) plasma concentrations of glucose, insulin, fructosamine, lipase, amylase, and tumor necrosis factor-α (TNF-α); 2) insulin sensitivity (IS); and 3) insulin signal transduction (IST) in insulin-sensitive tissues. Results: Low birth weight was not detected in the PEDO group. However, plasma concentrations of glucose, insulin, fructosamine, lipase, amylase, and TNF-α were increased and IS and IST were reduced (P <0.05) in the PEDO group compared with the CNO group. Conclusion: Maternal periodontal disease may induce insulin resistance and reduce IST in adult offspring, but such alterations are not attributable to low birth weight.
Keywords: Cytokines; Diabetes mellitus; Inflammation; Insulin resistance; Periodontal diseases; amylase; fructosamine; insulin; triacylglycerol lipase; tumor necrosis factor alpha; animal; birth weight; blood; female; glucose blood level; insulin resistance; male; metabolism; newborn; pathophysiology; periodontitis; physiology; pregnancy; pregnancy complication; prenatal exposure; radiography; rat; signal transduction; Wistar rat; Amylases; Animals; Animals, Newborn; Birth Weight; Blood Glucose; Female; Fructosamine; Insulin; Insulin Resistance; Lipase; Male; Periodontitis; Pregnancy; Pregnancy Complications; Prenatal Exposure Delayed Effects; Rats; Rats, Wistar; Signal Transduction; Tumor Necrosis Factor-alpha